1976
DOI: 10.1104/pp.58.3.438
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Malate Oxidation in Isolated Mung Bean Mitochondria

Abstract: Effects of ADP and ATP on products of malate oxidation in the presence or absence of respiratory inhibitors and an uncoupler were investigated in mitochondria isolated from mung bean (Phaseolus aureus var. Jumbo) hypocotyls. Changes in levels of products from malate oxidation generally correlated directly with changes in oxygen uptake. Effects of ADP and ATP were indistinguishable from each other when respiratory chain activity was limited. We concluded that adenylates indirectly act on malate oxidation via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…MDH activity is reversible and, in the mitochondrial matrix, the characteristics of malate oxidation strongly support the evidence that the regulation in vivo of MDH activity can be readily accounted for by equilibrium effect alone (2,20). MDH (2,20).…”
mentioning
confidence: 51%
“…MDH activity is reversible and, in the mitochondrial matrix, the characteristics of malate oxidation strongly support the evidence that the regulation in vivo of MDH activity can be readily accounted for by equilibrium effect alone (2,20). MDH (2,20).…”
mentioning
confidence: 51%
“…In the present study, we observed no stimulation in the rate of malate oxidation when ADP was added after uncoupling the mitochondria. We therefore conclude that the most straightforward explanation for the increase in oxaloacetate and pyruvate production brought about by ADP in coupled mitochondria is that it is primarily due to increased electron transport activity (2).…”
Section: Discussionmentioning
confidence: 99%
“…Since ADP increases the rate of electron transport and oxygen uptake in coupled mitochondria (3), higher rates of NADH oxidation will take place so that intramitochondrial NADH levels decrease and NAD+ increases (16). The equilibrium position of the malate dehydrogenase reaction is such that oxaloacetate production would be favored when NADH levels are low in the mitochondrial matrix (2,16). Therefore, in coupled mitochondria, ADP can control malate oxidation by regulation ofelectron transport activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations